Pengaruh Loyalitas Merek Dan Kualitas Produk Terhadap Minat Beli Sepeda Motor Honda (Studi Kasus Mahasiswa Prodi Manajemen Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya) - Mohamad Dimyati Hadi Saputra; Dovina Navanti; Franciscus Dwikotjo Sri Sumantyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
. The aim of this research is to determine the influence of Brand Loyalty and product quality on interest in purchasing Honda motorbikes. This research is quantitative research using a questionnaire method. The population used in this research were students from the Faculty of Economics and Business, Bhayangkara Jakarta Raya, University The sampling technique used in this research was Slovin sampling. In this research the dependent variable is Purchase Interest (Y), while the independent variables are Brand Loyalty (X1) and Product Quality (X2). For the validity test results used in Brand Loyalty product quality and purchasing decisions are valid, while the reality test results in this research show reliable results. The results of this research are that Brand Loyalty and Product Quality both partially and simultaneously influence Interest in Buying Honda motorbikes.